The effects of climate change on sea water intake and outfall systems in the Caspian sea - Uzun, Pelin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Climate change a ects sea level change which controls the wave and thermal mixing processes in the Caspian Sea (CS). The sea has been su ering from its unstable sea level due to climate change, which may be critical for the design and operation of Sea Water Intake Outfall (SWIO) systems. For the feasibility of a SWIO system, three processes are crucial: sea level, nearshore wave climate and thermal dilution. The scope of this thesis is the e ects of climate change on sea level, nearshore wave climate and thermal dilution in the CS. The changes in the Caspian Sea Level (CSL) due to climate change are predicted for the next century by using an unsteady 2D vertically integrated circulation model (RMA2). At the end of 2100, a decrease of 10.67 m in the Caspian Sea level is predicted. The Garabogaz Ammonia and Urea Production Plant is chosen as a sample case to examine the e ects of sea level change on SWIO systems in the CS. Nearshore wave climate and thermal dilution predictions are conducted using SWAN and CORMIX models for the same time periods, respectively. Operational problems are observed beginning in 2030 when there is intense wave breaking at the discharge location. Environmental constraints are jeopardized including the temperature di erence at 100 m downstream exceeding +30C in 2051. As a consequence, the SWIO system may seriously harm the environment in 32 years after construction. This situation shows the importance of predictions of the sea level, wave climate and thermal mixing processes in addition to standard design checks for the project lifetime. One solution to this problem could be constructing such systems on coasts with steeper slopes. The southern coast, the middle part of the western coast and north-west coasts of the eastern coast of the CS have steeper slopes.
Keywords: Climate change -- Caspian sea.